The role of people in the Customer Relationship Management (CRM) eco-system within South African private banks : an internal stakeholder perspective - Ramatong, Mpho Eugenia (My University, 2017)
Purpose: Private Banks are constantly seeking ways to build strong relationships with their most profitable customers. Despite this, there is limited research on CRM in the private banking industry of South Africa. The study assesses the role of internal stakeholders in the Customer Relationship Management (CRM) eco-system within South African in private banks. Design/Methodology/Approach: Drawing on the stakeholder and the resource based theories, the researcher conducted semi-structured in-depth interviews with a purposive sample of 20 research participants across the four leading private banks in South Africa. Findings: The research findings from the sample of 20 participants suggest that a highly skilled and experienced workforce is a primary driver of effective CRM implementation. Objectives and goals of the CRM eco-system have to be clear and employees need to be incentivised and motivated. Recommendations: Private banks need to continuously up-skill and retain experience employees in order to achieve high CRM objectives. Private banks need to have clear objectives and goals of implementing the CRM eco-system and employees need to be motivated and rewarded fairly for their contribution in successfully implementing the CRM eco-system. Implications: The internal stakeholders need to possess exceptional relationship management skills; have the ability to realise the importance of share of wallet; employ a customer-centric marketing approach; most importantly have a minimum experience of five years within the personal relationship banking industry. Key words and phrases: Customer Relationship Management (CRM), internal stakeholder, stakeholder theory, private banks, resource based view (RBV)
A research report submitted to the Faculty of Commerce, Law and Management, Wits Business School, University of Witwatersrand, Johannesburg South Africa. In fulfilment of the requirements for the degree Master of Management in Strategic Marketing
Keywords: Customer relations--South Africa--Management; Banks and banking--South Africa